Changes of libraries’ role in the context of the system theory - Juchnevič, Laura (Information & Media, 2015)
With this article, the author aims to theoretically justify the suitability of the systematic approach used in researching the change alternation of libraries’ roles, for finding solutions to real life problems (i.e., which roles must be taken by libraries in order to answer society’s needs). In humanitarian and social sciences, the systematic approach and the theory of systems are used for a thorough study of the object, while the soft systems methodology offers methods to study multiple and constantly changing social objects. In the article, a library is analysed as a complex system influenced by synergy processes; readers are introduced a possibility of conceptualising a library as a system according to the CIDOC CRM ontological model and presented with a programme for researching the change of libraries’ roles while using the soft system methodology.